Análise do perfil socioeconômico-cultural e da percepção de risco para a saúde quanto ao uso de esteróides anabolizantes em praticantes do fisiculturismo do estado de Sergipe - Santos, Josué Cruz dos (2024)
Introduction: Androgenic anabolic steroids called (AAS) are synthetic derivatives of testosterone initially used for therapeutic purposes although they have great potential in the treatment of various pathologies, assume a risk in the face of abuse. Currently, these substances are being used, in an abusive way, to improve performance in the middle of bodybuilding. Objective: This study aims to evaluate the socio-economiccultural profile and the state of health of bodybuilders in the State of Sergipe as well as to evaluate the knowledge of bodybuilders about the possible health risks promoted by excessive use of supplements and/or anabolic steroids. Methods: This is a study with the cross-sectional, descriptive-analytical method, "Survey" type (research) survey, the study population is finite and convenience type. The sample is composed of: individuals of both sexes, over 18 years old, self-declared as athletes of bodybuilding who lived in the State of Sergipe/ Brazil, participants in regional and/ or state competitions. Results: As a result, no significant associations were identified between sex (p=0.492), age (p=0.460) and family income (p=0.141) with medical follow-up. However, for the variables of educational level and the presence or absence of medical follow-up, a significant relationship was observed (p=0.01). Notably, 74.3% of the participants reported having medical follow-up, while 25.7% reported not performing such follow-up, and most belonged to the group with complete higher education. Regarding the use of substances, the steroids Sustanon 250 or Durateston, Nandrolone Decanoate (Deca or Deca Durabolin) and Testosterone Enanthe were the most mentioned by athletes. Regarding acute side effects, acne was reported by 33.8% (n=20) of the participants, followed by irritability with 32.1% (n=19) and alopecia (hair loss) and nervousness, both with 23.7% (n=14). For chronic side effects, the most frequently reported were hypertension with 36.0% (n=9), liver pathology with 28.0% (n=7) and cancer with 8.0% (n=2). Conclusion: highlights that the use of anabolic steroids (AAS) is widely disseminated among athletes, regardless of their socioeconomic profile. It is common to observe the combination of two or more types of AAS together, and prolonged use of these substances is frequent. Therefore, it is imperative to implement awareness campaigns that address the adverse effects of AAS in the body, aimed at both high-performance athletes and recreational athletes. These initiatives are essential to promote a more comprehensive understanding of the risks associated with the use of AAS and to encourage safer and healthier practices within the sports community.